Two new records of Epitoniidae from Easter Island, Chile - Brown, Leonard; Raines, Bret (Zootaxa, 2004)
While dredging off the coast of Easter Island, two species of Epitoniidae were discovered, which have not been previously reported, Epitonium (Parviscala) deificum (Melvill & Standen, 1903), a species previously known from the Red Sea, Gulf of Oman and Hawaii, and Opalia (Opalia) sumatrensis (Thiele, 1925) a species previously known from Padang, Sumatra, and are the first epitoniids to be reported from the island in nearly twenty-five years.